A swept‐intersection‐based remapping method in a ReALE framework. (13th December 2012) - Harribey, Thibault; Breil, Jérôme; Maire, Pierre‐Henri; Shashkov, Mikhail
SUMMARY A complete reconnection‐based arbitrary Lagrangian–Eulerian (ReALE) strategy devoted to the computation of hydrodynamic applications for compressible fluid flows is presented here. In ReALE, we replace the rezoning phase of classical ALE method by a rezoning where we allow the connectivity between cells of the mesh to change. This leads to a polygonal mesh that recovers the Lagrangian features in order to follow more efficiently the flow. Those reconnections allow to deal with complex geometries and high vorticity problems contrary to ALE method. For optimizing the remapping phase, we have modified the idea of swept‐integration‐based. The new method is called swept‐intersection‐based remapping method. We demonstrate that our method can be applied to several numerical examples representative of hydrodynamic experiments.Copyright © 2012 John Wiley & Sons, Ltd.